2013
DOI: 10.1016/j.mce.2013.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific Leptin promoter DNA methylation is associated with maternal and infant perinatal factors

Abstract: Leptin a regulator of body weight is involved in reproductive and developmental functions. Leptin promoter DNA methylation (LEP) regulates gene expression in a tissue-specific manner and has been linked to adverse pregnancy outcomes. In non-pathologic human pregnancies, we assessed LEP methylation, genotyped the single nucleotide polymorphism (SNP) rs2167270 in placental (n=81), maternal and cord blood samples (n=60), and examined the association between methylation, genotype, and perinatal factors. Maternal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
86
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 56 publications
7
86
3
2
Order By: Relevance
“…Lesseur et al found that small for gestational age (SGA) newborns had higher DNAm levels in LEP promoter region (see genomic location in Fig. S2 -Lesseur) in cord blood cells 34 ; directionally concordant with our observation that higher DNAm at LEP is associated with lower leptin levels and lower birth weight. This is also consistent with previous functional studies of leptin expression regulation in adipocytes during differentiation: pre-adipocytes showed high DNAm levels, LEP promoter was almost fully unmethylated in mature adipocytes, and demethylation of specific CpG sites in LEP promoter was essential for leptin expression.…”
Section: Discussionsupporting
confidence: 91%
“…Lesseur et al found that small for gestational age (SGA) newborns had higher DNAm levels in LEP promoter region (see genomic location in Fig. S2 -Lesseur) in cord blood cells 34 ; directionally concordant with our observation that higher DNAm at LEP is associated with lower leptin levels and lower birth weight. This is also consistent with previous functional studies of leptin expression regulation in adipocytes during differentiation: pre-adipocytes showed high DNAm levels, LEP promoter was almost fully unmethylated in mature adipocytes, and demethylation of specific CpG sites in LEP promoter was essential for leptin expression.…”
Section: Discussionsupporting
confidence: 91%
“…18 For example, in utero exposure to famine and gestational diabetes has been associated with offspring LEP promoter hypermethylation in blood of adults 11 and placental LEP hypermethylation, 19 respectively. According to Lesseur et al, 12 cord blood LEP methylation was higher in small for gestational age infants and lower in infants born to pre-pregnancy obese mothers. Modifications in the profile of leptin in early life may contribute to the lower expression of appetite regulators, alter fetal neural development, and, in the end, alter the susceptibility to obesity and metabolic disorders in adulthood.…”
Section: Discussionmentioning
confidence: 97%
“…LEP promoter DNA methylation has been linked to adverse pregnancy outcomes and is plausibly involved in fetal metabolic programming. 12 Another metabolic gene that can be affected by maternal nutrition is the retinoid X receptor a (RXRA) gene, which is known to be involved in insulin sensitivity, adipogenesis, and fat metabolism. Lower maternal carbohydrate intake in early pregnancy was associated with higher RXRA cord blood methylation and with greater offspring's adiposity (fat mass and percentage fat mass) in 9-year old children.…”
Section: Introductionmentioning
confidence: 99%
“…Studies linking genetic variability and race or ethnicity and epigenetic mechanisms have been limited. Where studies have examined genetic variation and epigenetics, they have generally focused on candidate genes involved in metabolism of folate or the pathways involved in the epigenetic mechanism, or in some cases on specific relationships between genetic variants within a gene and their epigenetic consequences (Bromer et al, 2013;Klengel et al, 2013;Lesseur et al, 2013;Paquette et al, 2013). There have been suggestions of differences in DNA methylation by race and ethnicity (Terry et al, 2008), although strong examinations that can control for the confounding factors of environment and race have not yet been undertaken, and are an important area to consider.…”
Section: Additional Factors Influencing Epigeneticsmentioning
confidence: 99%